Impact of crimson clover dying mulch on two eggplant insect herbivores. (2nd May 2012) - Hooks, C. R. R.; Hinds, J.; Zobel, E.; Patton, T.
Abstract Eggplant Solanum melongena L., is often colonized by two early season insect defoliators. The Colorado potato beetle (CPB), Leptinotarsa decemlineata (Say), and flea beetles Epitrix spp., emerge from their overwintering sites in early spring and seek out emerging host plants such as eggplant. During the 2009 and 2010 growing season, field studies were conducted to investigate the impact of inter‐planting eggplant into a crimson clover (CC), Trifolium incarnatum L., winter cover crop on populations of flea beetles, CPB and their associated arthropod predators. The experiment consisted also of two levels of insecticide usage such as an application of azadirachtins plus pyrethrins followed by several applications of spinosad or no insecticide sprays as subplot treatments. During both study years, significantly fewer (adults, larvae and egg masses) were found on eggplant inter‐planted into CC than in bare‐ground (BG) eggplant plots. Although flea beetle abundance was greater in BG eggplant during 2010, they appeared to be less influenced by the presence of CC than were CPB. Additionally, there was no apparent impact of insecticide treatment on CPB populations on eggplant inter‐planted into CC. However, there was a decline in CPB following treatments with insecticides in BG eggplant plots. This suggests that a winter cover crop such as CC can be used to help manage CPB in eggplant, however, using this tactic in tandem with insecticide sprays may not result in greater CPB management.